Panen Air Hujan di Kampus Universitas Diponegoro - Nurrohman, Faisal; Waskita Eka Paksi, Satria; Sangkawati Sachro, Sri; Sugiyanto, Sugiyanto (Department of Civil Engineering, Diponegoro University, 2014)
The design of rainwater harvesting is planned for alternative water source in Universitas Diponegoro area and hopefully it can reduce the use of groundwater as the main source water to fill the demand of water in Universitas Diponegoro Tembalang area. The use of groundwater to fill the water demand in Universitas Diponegoro Campus for years 2014/2015 of 2.23 lt/dt it more than the optimum discharge are allowable to take the water wells is equal to 0.2-1 lt/dt. Based on that the planning of the rainwater harvesting building is made of with a volume of 245 m3 with a dimensions of 7m x 7m x 5m and dimensions of infiltration wells with a diameter of 1.5 and depth of 3m. Planning of the rain water harvesting in the Universitas Diponegoro Tembalang area the cost of Rp 275,465,000,- with the process of work for 29 days.